Book review: Darnell, Simon C. 2012: Sport for development and peace: A critical sociology. (July 2015) - Fontefrancesco, Michele Filippo
Darnell, Simon C. 2012: Sport for development and peace: A critical sociology . London and New York: Bloomsbury Academic. 182 pp. £50.00 hardcover. ISBN: 9781849663441.